Oil price shock and macroecomomic aggregates: Empirical evidence from Nigeria using the structural vector autogregressive (SVAR) approach - ADESETE, Ahmed Adefemi; BANKOLE, Fatima Abiodun (Journal of Economics Library, 2020)
Abstract. The continual fluctuation in oil price has continued to be a source of concern for economists and policymakers, both in Nigeria and abroad, given its sudden implications on existing and future policy plans as well as on some macroeconomic indicators. The Nigerian economy is an oil-dependent one and has about 90% of its export earnings come from oil and so is highly vulnerable to the sudden changes in oil prices either positive or negative. This paper evaluates the relationship between this unanticipated changes in oil price and some selected macroeconomic aggregates in Nigeria using the structural vector autoregressive (SVAR) methodology while employing its impulse response functions, to further explore the impact of oil price shock on the Nigerian economy over different time period. The SVAR result shows that oil price shock has a negative impact on all of the selected macroeconomic indicators such as economic growth, import, investment, inflation, and the exchange rate except export in the long term. Furthermore, the impulse response functions shows that the response of all selected macroeconomic indicators in this study to oil price shock were mixed but mostly negative over a time period of 12 months. The ADF unit root test confirmed that all series were stationary at I(1) only except inflation rate which was I(0) and I(1). The autocorrelation LM and White heteroscedasticity test confirms the non-rejection of the null hypothesis concluding that the residuals from the SVAR model were not serially correlated and homoscedastic. Based on the findings the study recommended the diversification of the economy to other key sectors such as agriculture and mining to help reduce the over-reliance on crude oil earnings also, measures should be taken to lower the cost of production for crude oil per barrel to minimize the impact of oil price shock on macroeconomic indicators. Keywords. Oil price shock, Macroeconomic indicators, SVAR Models, GDP, Impulse Response, Exchange rate, Inflation. JEL. C32, E30, F41.